2013
DOI: 10.3386/w19702
|View full text |Cite
|
Sign up to set email alerts
|

After the Drought: The Impact of Microinsurance on Consumption Smoothing and Asset Protection

Abstract: All errors are our own. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 5 publications
1
29
0
3
Order By: Relevance
“…An important disadvantage is basis risk (see below). In this 33 review paper we discuss the determinants of demand for index-insurance, the impact of 34 index-insurance on smallholder livelihoods, and the existing links between index-insurance 35 and credit. In this meta-analysis, we identify key discoveries on the potential of index-36 insurance in enhancing credit supply for smallholders and thus farm productivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An important disadvantage is basis risk (see below). In this 33 review paper we discuss the determinants of demand for index-insurance, the impact of 34 index-insurance on smallholder livelihoods, and the existing links between index-insurance 35 and credit. In this meta-analysis, we identify key discoveries on the potential of index-36 insurance in enhancing credit supply for smallholders and thus farm productivity.…”
mentioning
confidence: 99%
“…23 24 In this section, three key factors, comprising twelve indicators, that help explain demand for Table 1, 2 and 3 in the Appendix. 34 …”
mentioning
confidence: 99%
“…This strategy, frequently used by farmers to cope with shocks (Janzen and Carter 2013), has been found to have pernicious effects on household welfare (Hill 2011) and lower households' ability to escape poverty (Lunde 2009). …”
Section: Agricultural Risk Management and Strategiesmentioning
confidence: 99%
“…4 The implication is that agricultural investments are risk constrained in this population and that index insurance successfully relaxes that constraint, perhaps more effectively than cash transfers. Janzen and Carter (2013) study the same index based livestock insurance product in Kenya that we explore. They find that, in the wake of indemnity payments triggered by a massive drought, wealthy households with insurance foresee selling fewer livestock (their main productive capital) than their uninsured counterparts and that poor insured households expect to reduce consumption less in the coming periods than the uninsured poor.…”
Section: Social Insurancementioning
confidence: 99%
“…Previous studies from the region have found that herd size is related to coping strategies (Carter & Lybbert 2012;Janzen & Carter 2013), productivity , livestock mortality rate (Lybbert et al 2004), and willingness to pay (Chantarat et al 2014). To better understand the distribution of impacts, we estimate the expected impacts allowing for variation in the average marginal impact of participation, and variation in participation rates across initial herd size (Appendix G).…”
Section: Heterogeneity In Impacts and Program Interactionsmentioning
confidence: 99%